A Clash of Histories: Encounters of Migrant and Non-Migrant Laborers in the Canadian Automobile Parts Industry - Leach, Belinda (Journal of Global and Historical Anthropology, 2008)
This article considers the confrontations between immigrant and non-immigrant workers in the workplace and the implications of these confrontations for workplace unity and class formation. Contributing to scholarship at the intersection of history, class, and migration, the article argues that workers bring to work histories that are constructed as oppositional. The roots of these oppositions lie in shared but different histories of dispossession and migration, masked by dominant cultural and class narratives, which privilege non-immigrant histories that are class-based, masculinist, and nationalist, and subordinate those of immigrants. In the process, neo-liberal agendas are bolstered. Questions of how such processes take place are important for understanding class formation within societies with large immigrant populations.
Keywords: class; gender; history; migration

Contingent Work, Disrupted Lives: Labour and Community in the New Rural Economy - Winson, Anthony; Leach, Belinda (Studies in comparative political economy and public policy, 2002)
[E]xamines the effects of economic globalization on several manufacturing-dependent rural communities in Canada. In looking at such contemporary corporate strategies as plant closures and downsizing, authors [The authors] consider the impact of capitalist restructuring on the residents of various communities. [They] argue that the new rural economy has caused considerable instability and hardship in the lives of rural residents as they struggle to adapt in the face of economic upheaval."--Publisher's description. Contents: The Global and the Local: Understanding Globalization through Community Research -- Community Sketches, History, and Method -- The New Rural Economy and the Shape of Restructuring -- Skidding into the Contingent Work World -- 'Forget All Your Dreams and Good Luck with Your Life': Lay-Off and the New Reality of Contingent Labour -- Economic Diversity, Sustainability, and Manufacturing Communities. Geographic: Ontario. Ontario. Includes bibliographical references (pages 205-220) and index.
Keywords: Aspect social; Ontario. Chômage en milieu rural; Ontario. Deindustrialization; Ontario. Deindustrialization. Displaced workers. Globalization; Ontario. Desempleo; Ontario. Displaced workers; Ontario. Désindustrialisation; Ontario. Globalization; Ontario. Industrie rurale; Ontario. Mondialisation; Ontario. Rural industries; Ontario. Trabajadores; Ontario. Travailleurs; Ontario. Travailleurs licenciés; Ontario. Working class; Rural unemployment; Social aspects; Social aspects. Rural industries. Rural unemployment. Working class. Landwirtschaft. Arbeitslosigkeit